Analisis Tingkat Penggunaan Gadget pada Anak Usia Dini dengan menggunakan K-Mean - Khaerul Anam; Rizal Rusyana; Bani Nurhakim; Denni Pratama (Universitas Wahid Hasyim, 2024)
The use of gadget devices in early childhood has become an increasing concern in recent years. influence on human thinking patterns because devices can find data quickly for children. Research on the consequences of using gadgets in early childhood has its own significance in understanding its impact on their development. In this study, an analysis was carried out on the level of gadget use in early childhood by applying the K-Means algorithm. The K-Means algorithm is used to group the level of gadget use in children, allowing the identification of groups that have similar characteristics. The aim of this research is to evaluate and understand the level of gadget usage by young children in response to technological developments, as well as to develop an effective method or approach in classifying their gadget usage patterns by utilizing the K-Means algorithm. Thus, this research aims to provide in-depth insight into gadget use patterns in young children, which can be the basis for developing better strategies or policies regarding technology use in this age group. From a total of 332 questionnaire responses, 14 groups were found based on the best DBI scores with different category distributions, namely